Apoptotic Killing and Phagocytosis of Host Cells by the Parasite Entamoeba histolytica - Huston, Christopher D. (American Society for Microbiology, 2003)
The ability of Entamoeba histolytica to kill and phagocytose host cells correlates with parasite virulence. This study addressed the role of apoptotic cell killing and host cell phosphatidylserine exposure in the subsequent phagocytosis of Jurkat T cells by E. histolytica. Ingested host cells were apoptotic, as evidenced by the activation of caspase 3 in 88% ± 3% (mean and standard deviation [SD] of the mean) of Jurkat cells engulfed by E. histolytica; ingested cells without detectable active caspase 3 were already disrupted and partially digested. That apoptotic cell killing preceded phagocytosis was supported by the demonstration that a higher percentage of amebae ingested apoptotic cells than ingested healthy cells (62% ± 7% versus 30% ± 9%, respectively [mean and SD]) (P = 0.008). E. histolytica also ingested apoptotic Jurkat cells more rapidly than necrotic control cells (8.5% ± 0.4% versus 3.5% ± 0.7%, respectively [mean and SD]) (P < 0.001). The inhibition of amebic cytotoxicity with d-galactose (which blocks the amebic Gal/GalNAc lectin) blocked the phagocytosis of healthy cells by greater than 80%, providing further evidence that apoptosis preceded engulfment. In contrast, d-galactose blocked the phagocytosis of already apoptotic cells by only 40%, implicating an additional host ligand (besides d-galactose) in amebic engulfment of apoptotic cells. The most characteristic surface change on apoptotic cells is phosphatidylserine exposure. Consistent with a role for host cell phosphatidylserine exposure in amebic ingestion of killed cells, Jurkat cell phosphatidylserine was exposed during incubation with E. histolytica (27% ± 1% [mean and SD] specific increase at 30 min) (the P value versus the control was 0.0003). Approximately 50% more amebae ingested viable Jurkat cells expressing phosphatidylserine on the outer leaflet of the plasma membrane than ingested control cells (30.3% ± 2.2% versus 19.8% ± 1.9%, respectively [mean and SD]) (P = 0.003). By analogy with phagocytic clearance during apoptosis in metazoans, amebic apoptotic host cell killing followed by phagocytosis may limit inflammation and enable amebae to evade the host immune response.